2020
DOI: 10.1007/s13555-020-00416-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of 18 Patients with Psoriasis and Multiple Myeloma Identified Through Digital Health Crowdsourcing

Abstract: Psoriasis is a skin condition that affects over 100 million people worldwide, while multiple myeloma (MM) accounts for 10% of all hematologic malignancies in the US. There has been limited research on the intersection of psoriasis and MM, and clinicians often face difficult decisions in treating patients diagnosed with both conditions. For instance, the management of psoriasis with systemic immunotherapies in MM patients can be challenging because of concern about immunosuppression and possible worsening of MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…All the articles were retrieved according to the algorithm presented in Figure 1. Finally, five original manuscripts were analyzed, including three case series and two case reports, that are summarized in Table 1 6‐10 . A total of 10 patients affected by psoriasis and treated with IL‐17A inhibitors were found, with a median age of 59 years, IQR 51‐63 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the articles were retrieved according to the algorithm presented in Figure 1. Finally, five original manuscripts were analyzed, including three case series and two case reports, that are summarized in Table 1 6‐10 . A total of 10 patients affected by psoriasis and treated with IL‐17A inhibitors were found, with a median age of 59 years, IQR 51‐63 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, five original manuscripts were analyzed, including three case series and two case reports, that are summarized in Table 1. [6][7][8][9][10] A total of 10 patients affected by psoriasis and treated with IL-17A inhibitors were found, with a median age of 59 years, IQR 51-63 (Table 1). About 9 out of 10 patients had a prior malignancy in current clinical remission, whereas one had a metastatic cancer at the time of IL-17A inhibitor therapy for psoriasis.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…22 Therefore, HealthTree Cure Hub practices a patient-input and medical consultant-verified approach to maximize the potential for population-based analyses and to draw reliable conclusions. As a result, we have published nine abstracts, seven to ASCO [23][24][25][26][27][28][29] and two to the American Association of Cancer Research, 30,31 and published one peer-reviewed manuscript in Dermatologic Therapy, 18 with others in preparation.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have resulted in 10 scientific publications (nine abstracts and one manuscript). 18 Hurdle 3: High Costs to Answer Research Questions High costs are associated with disease research. 10 HealthTree Cure Hub provided easy, complete, and free access to patient data, which enabled researchers to answer relevant questions that are not traditionally funded by industry or the federal government.…”
Section: Hurdle 2: Shallow Datamentioning
confidence: 99%
“…101 In their review, they identified a total of 10 patients, seven of whom were treated with secukinumab, one treated with ixekizumab, and two treated with both sequentially. [102][103][104][105][106]…”
Section: Malignanciesmentioning
confidence: 99%